Experimental dapsone administration induces infertility in male Wistar rats: Mechanisms and clinical implications. Issue 3 (September 2019) - Akinsomisoye, Olumide Stephen; Gupta, Gopal; Raji, Yinusa
Abstract: Dapsone (4, 4′-diaminodiphenylsulfone, DDS) is a potent anti-inflammatory and antibacterial compound which has been used in the treatment of leprosy, vasculitis and dermatitis herpetiformis, lupus erythematosus profundus and even as an antimalarial in combination with proguanil. This study investigated the effect of the administration of dapsone on the reproductive activities of male rats using in vivo and in vitro techniques. In the in vivo study, dapsone was administered orally to male Wistar rats for 5 days or 6 weeks after which their body weight, relative reproductive organ weights, sperm parameters and reproductive hormones were determined while testicular and epididymal histology were also assessed. Data were compared using analysis of variance and Students-Newman-Keuls multiple comparison test. For the in vitro study, Sertoli cells were cultured and treated with varying doses of dapsone at different durations, thereafter Sertoli cell viability and nuclei integrity were determined. Also, the genetic expressions of Glial cell line-derived neurotrophic factor (GDNF) and transferrin were assessed. The results obtained from the in vivo study showed a duration-dependent significant decrease in body and reproductive organ weights, sperm parameters and serum testosterone concentration. Testicular and epididymal histology also showed duration-dependent degenerative changes. However, all these changes were restored towards control values in the recovery experiment. The viability and deoxyribonucleic acid (DNA) integrity of the treated Sertoli cells showed dose and duration-dependent adverse effects while GDNF and transferrin showed normal genetic expressions. These results suggest that dapsone could induce male reproductive stress by affecting testicular and epididymal structure and function.